A systematic review and embryological perspective of pluripotent stem cell-derived autonomic postganglionic neuron differentiation for human disease modeling - Thomas A Bos; Elizaveta Polyakova; Janine Maria van Gils; Antoine AF de Vries; Marie-José Goumans; Christian Freund; Marco C DeRuiter; Monique RM Jongbloed (eLife)
Human autonomic neuronal cell models are emerging as tools for modeling diseases such as cardiac arrhythmias. In this systematic review, we compared 33 articles applying 14 different protocols to generate sympathetic neurons and 3 different procedures to produce parasympathetic neurons. All methods involved the differentiation of human pluripotent stem cells, and none employed permanent or reversible cell immortalization. Almost all protocols were reproduced in multiple pluripotent stem cell lines, and over half showed evidence of neural firing capacity. Common limitations in the field are a lack of three-dimensional models and models that include multiple cell types. Sympathetic neuron differentiation protocols largely mirrored embryonic development, with the notable absence of migration, axon extension, and target-specificity cues. Parasympathetic neuron differentiation protocols may be improved by including several embryonic cues promoting cell survival, cell maturation, or ion channel expression. Moreover, additional markers to define parasympathetic neurons in vitro may support the validity of these protocols. Nonetheless, four sympathetic neuron differentiation protocols and one parasympathetic neuron differentiation protocol reported more than two-thirds of cells expressing autonomic neuron markers. Altogether, these protocols promise to open new research avenues of human autonomic neuron development and disease modeling.